The Constitutional Court of the Republic of Indonesia in the digital era: a challenge to uphold justice for all Indonesian people - Adhani, Hani; Mokhtar, Khairil Azmin (On İki Levha Yayincilik A. Ş, 2019)
After Indonesia‘s reform in 1998, one of the essential points in the Indonesian constitutional system was the amendment of the Indonesian Constitution. The results of the amendment eventually resulted in new state institutions aimed at supporting the effects of reforms. One of them is the Constitutional Court. The Constitutional Court stipulated in Article 24C The Indonesian Constitution is the only state institution that is tasked with safeguarding Indonesia‘s constitution and democracy. Of course, the heavy duty carried out by the Constitutional Court is not only a burden and the work of nine Constitutional Justices. The Indonesian Constitutional Court which was established on August 13, 2003, strives to become an institution that can not only be trusted by the Indonesian people but also become a modern state institution. This was recorded in the blueprint of the Indonesian Constitutional Court and also written in the vision and mission of the Indonesian Constitutional Court. With the population of Indonesia reaching 260 million and spread across almost 17,000 islands, then to introduce the Constitutional Court quickly and accurately to the community must be assisted with special tools called technology, especially digital technology. In this study, the author will try to examine and explain how the efforts made by the Constitutional Court as a new court institution in charge of safeguarding the constitution and democracy and protecting human rights. So that they can be easily recognised by the public through digital technology aids so that the Indonesian population 260 million spread across various islands can easily find out about the Constitutional Court and can easily submit a request or claim to the Constitutional Court as an effort to safeguard the constitutional rights of Indonesian citizens.